Perilaku Menyimpang Remaja dan Solusinya dalam Persepektif Bimbingan Konseling Islam - Sefi Andika (Institut Agama Islam (IAI) Nurul Hakim, 2023)
Urgency Of Guidance And Counseling For Teens. The adolescent world is a world full of interesting dynamics. Generally, they want new things that have never been tried during this time. Something new if it has implications for positive actions is certainly not a problem, but if it leads to negative acts that would cause problems. Teenagers who have a problem and can solve their own problems then it is positive. However, on the contrary, they have a problem and can not solve it alone and take it to negative acts which means they need the help of others. Simply put from the perspective of guidance and counseling, the person who helped solve the problems of others is called a counselor. The counselor is expected to help troubled teens to find a solution that best suits the light and severity of the problems faced by the youth. Further technical handling of juvenile deviant behavior is: first, individual handling including giving instructions or advice, counseling, and psychotherapy, secondly, the handling of family, third, and fourth treatment group handling partner.